2020
DOI: 10.18632/aging.103960
|View full text |Cite
|
Sign up to set email alerts
|

Resemblance and differences in dietary restriction nephroprotective mechanisms in young and old rats

Abstract: Dietary restriction (DR) is the strategy ameliorating the morbidity of various pathologies, including age-associated diseases. Acute kidney injury (AKI) remains a problem for the elderly with DR being a promising approach for diminishing its consequences. We evaluated the possible nephroprotective potential of short-term DR in young and old rats. DR in young rats resulted in pronounced beneficial effects normalizing lipid metabolism (triglycerides concentration, adiponectin level) activating autophagic-lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 107 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…Thus, it is not easy to attribute the ultrastructure of mitochondria to their quality, but we can assume that the predominant condensed state of the mitochondrial matrix in cells taken from young animals may correspond to a more active turnover of ATP, which leads to a higher activity of ATP synthase associated with active proliferative capacity. Earlier, we underwent the analysis of mitochondrial ultrastructure in tubular renal cells, confirming the partial rejuvenating effect of diet restriction [ 38 ]. While the mitochondria in MSC taken from young animals had a condensed configuration, in cells from old rats, the configuration shifted to a more orthodox state, which we interpreted as a transition to a state of mitochondria with lower membrane potential.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, it is not easy to attribute the ultrastructure of mitochondria to their quality, but we can assume that the predominant condensed state of the mitochondrial matrix in cells taken from young animals may correspond to a more active turnover of ATP, which leads to a higher activity of ATP synthase associated with active proliferative capacity. Earlier, we underwent the analysis of mitochondrial ultrastructure in tubular renal cells, confirming the partial rejuvenating effect of diet restriction [ 38 ]. While the mitochondria in MSC taken from young animals had a condensed configuration, in cells from old rats, the configuration shifted to a more orthodox state, which we interpreted as a transition to a state of mitochondria with lower membrane potential.…”
Section: Discussionmentioning
confidence: 83%
“…Within these frames, reducing energy expenditure in its practical form, expressed as caloric restrictions, can potentially lead to a longer existence of the biological system, and at least slow down the aging process [ 54 ]. To some extent, the lower energy yield observed in this study in pMSC, due to the change in contribution of the glycolytic pathway to the total metabolism, is able to provide both adaptive healthy properties [ 38 ] and a longer life [ 55 ]. Ultimately, presumably acquired anti-senescence mechanisms in stem cells may provide the speed of aging at a rather low level, which requires further detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed in the renal model of I/R, that in old rats DR for 1 or 2 months was not as effective as in young and did not reduce AKI measured by the level of serum creatinine and urea, as well as NGAL level in urine (Andrianova et al, 2018(Andrianova et al, , 2020. The loss of DR effectiveness during aging is more likely to have a gradual pattern since in 12-month-old rats DR still demonstrated some nephroprotective effect, but to a lesser extent than in young animals (Andrianova et al, 2020).…”
Section: Dietary Restriction In Old Animalsmentioning
confidence: 78%
“…Most fruitful experimental studies of various DR protocols have been conducted in young animals (Singh and Krishan, 2019), while a few studies of DR protection in renal injury have shown a decline in beneficial effects with age (Andrianova et al, 2018(Andrianova et al, , 2020. This raises the question of implementation of DR in clinical practice since elderly people predominate among patients with AKI, so additional studies are needed to improve the effectiveness of DR for the aged kidney.…”
Section: Possible Mechanisms Of Dietary Restriction Impairment During Agingmentioning
confidence: 99%
See 1 more Smart Citation